Adaptive Forwarding and Routing of Named Data Networking A Survey - Ade Aditya Ramadha; Leanna Vidya Yovita; Tody Ariefianto Wibowo; Ilmi Aulia Assyifatunisa (Centre for Research and Development on Resources, Equipment, and Operations of Posts and I, 2023)
In recent years, Named Data Networking (NDN) has been one of the future internet network architectures by proposing it as a substitute for existing IP networks. NDN assigns addresses/names to data or content, whereas IP assigns addresses to devices. NDN router has a Content Store (CS) component to store requested packets and reducing the time for duplicate content requests. As network architecture, NDN uses several algorithms and strategies in the process. This paper will specifically discuss the forwarding and routing algorithm. Forwarding mechanisms play a significant role in packet delivery on the NDN system. Even though routing was not the main component of the NDN system, the routing mechanism and Routing Information Base remain important, considering Forwarding Information Base was generated after Routing Information Base was generated. Routing has significant control, whereas forwarding can give finer control over the delivery path. Considering the previous statement, the combination of routing and forwarding strategy must be considered to optimize the performance of the packet delivery system on NDN. In addition to getting information about the entire network, centralized routing, and adaptive networking are needed to distribute all network traffic fairly. The challenges and opportunities can also be a reference and a guideline for future Adaptive NDN research.